Critérios para priorização de intervenções de manutenção em pavimentos rodoviários - Serafini, Lauson (2005)
In this study, practical applications involving the use of different procedures, considered in the previous studies for the priorization of maintenance interventions in paved networks are described. The main reasons that had motivated to carry out the research were the insufficiency of the available financial resources to keep the pavements in acceptable conditions and the absence of rational procedures adjusted for priorization of the investments to be accomplished in one network paved. It is presented, still, a discussion about the finding results of the application of priorization procedures, which contemplates distinct methologies for identification of the interventions priorities of maintenance, to be accomplished along the time in structures of pavements. Such analysis was accomplished in a paved network of the Rio Grande do Sul, called Lote 01 with 234.95 miles in 31 road stretches. Through This study it was possible to conclude that the priorization procedures, even so sufficiently usenful, need to be improved with the inclusion of models of performance prediction in this original form